Corporate Leverage and its Impact on Profitability and Shareholder Value Creation in the Indian Textile Sector - Vijayalakshmi, D.; Manoharan, Padmaja (Indian Journal of Finance, 2014)
Shareholder value creation has become the trait of corporate dialect. The LPG era has made a drastic change in the financing policies of the corporate firms warranting a redesign in their capital structure. Leverage plays an essential role in framing the capital structure. The focal gain of the insertion of fixed cost funds in the capital structure has a domino effect on higher profits. The textile sector is a capital intensive sector, where a greater emphasis has been given in framing the capital structure. In this backdrop, the present study made an attempt to examine the impact of leverage on profitability and shareholder value creation in the Indian textile sector for the period from 1995-96 to 2009-10. A panel data approach was applied to analyze the data. The study revealed that leverage had a significant influence on profitability, and the sector has to concentrate on enrichment of shareholders’ wealth.